Corporate sustainability and firm financial performance – the mediating effect of board gender diversity - Tamminen, Satu (My University, 2016)
The thesis investigates the relationship between corporate sustainability performance and firm financial performance. Firms are facing new business challenges as the ideology is shifting from shareholder maximization to satisfy the needs of multiple stakeholders. Therefore, sustainability practices should be included in business strategy to achieve financial competitive advantages as well. Furthermore, prior literature suggests that board of directors have an important role on firm success. Thus, one board component, gender diversity, is included in the empirical analysis. In contrast to prior research, the thesis investigates the different dimensions of corporate sustainability performance separately, and not only the overall sustainability. Moreover, little research investigates what components affect the relationship between corporate sustainability and financial performance. The aim is to fill this gap in the literature. Using financial data of the S&P 1500 firms and ESG data provided by ASSET4, the study finds a significant positive relationship between corporate sustainability performance and profitability, as measured by ROA and ROE. In addition, the results suggest that female directors strengthen the positive relationship between corporate sustainability and profitability. In contrast, the results report a negative association of corporate sustainability performance with firm value, as measured by Tobin’s Q. The relationship remains negative and statistically significant also after including board gender diversity variable. The findings are consistent with several studies highlighting the importance of sustainability and nonfinancial performance. Furthermore, a more diverse board is able to respond to the variety of stakeholders’ needs that will eventually give financial benefits as well. Further research is required to gain a better understanding of the circumstances and components that have an impact, positive or negative, on the relationship between firm nonfinancial and financial performance.
Keywords: Corporate sustainability performance; firm financial performance; ESG; board gender diversity; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|